Relationship between Group Cohesiveness and Interpersonal Communication on Organizational Commitment of Elementary School Teachers in the Dahlia Cluster - Junaidi Junaidi (Yayasan Ilomata, 2021)
This study aims to explain the results of empirical studies regarding the relationship between group cohesiveness and interpersonal communication with organizational commitment. This research is a correlational quantitative research type because it aims to determine the direction and magnitude of the relationship between the variables studied. The research subjects were 115 elementary school teachers in the Dahlia cluster. Collecting data using questionnaire techniques, observation, interviews and documentation. Testing the research hypothesis using correlation analysis, regression and correlation. The results showed that there was a relationship between group cohesiveness and interpersonal communication with organizational commitment resulting in a regression equation Ŷ = 77.850 + 0.410X1 + 0.810X2. And among the variables that have the most influence on organizational commitment is work motivation at 36.4% from group cohesiveness of 26.9%. Based on these results, teachers should increase group cohesiveness and interpersonal communication. With the improvement of these two things it is expected that organizational commitment can increase